Deconstructing resilience: why gender and power matter in responding to climate stress in Bangladesh. (7th February 2019) - Jordan, J. C.
Abstract : Resilience is increasingly becoming the new buzz word. This paper examines the utility of the concept of resilience for understanding the gendered experiences of women to climate stress, through case study research in South-west Bangladesh. It provides evidence that resilience, as commonly understood, is inadequate for understanding the intersecting vulnerabilities that women face because of embedded socio-cultural norms and practices. These vulnerabilities culminate in a gendered experience of climate stress, where some groups of women are more likely go without education, food and access to good quality water. Such circuits of control highlight the importance of a more radical, transformational, gendered and power sensitive frame for moving beyond coping mechanisms to strategies that deal with the fundamental root causes of vulnerability to climate stress. A failure to do so risks further reinforcing gender inequalities due to the reality of social difference and inequities within local power structures.